Prison libraries of Tobolsk province in the XIX century - N. I. Zagorodnyuk (Библиосфера, 2018)
The article objective is to trace the process of prison libraries formation and features of their functioning in the XIX century under conditions of changing the Russian penitentiary system evidently for Tobolsk province. The first mention of the libraries is at the beginning of the XIX century. The author shows the book functioning process under prison conditions, its role in prisoners’ life, the first libraries formation as repositories of books and their activity, features of the educational work forms, relationship with the church and school. The initiative of distributing books of spiritual content among prisoners belongs to the church. The Bible Society played a certain role distributing the Bible and St. Scripture at the early XIX century everywhere, including prisons. At the initial stage libraries have been formed at prison churches, which book collections included literature of spiritual and moral content. Opening schools, the book collections got fiction, popular scientific literature on natural sciences and humanities. At the late XIX century every prison castle had own library working in close connection with the church: reading, conversations of spiritual and moral content, loud reading books by literate prisoners. Besides, the book performed leisure functions, contributed to the individual socialization.